A Canadian replication of Telep and Lum’s (2014) examination of police officers’ receptivity to empirical research - Blaskovits, Brittany (Policing and society, 2020)
Research conducted in the United States (U.S.) suggests that many police professionals are unaware of, or resistant to, empirical research, and see little value in adopting evidence-based approaches for tackling policing issues. To determine whether similar views are held by Canadian police professionals, 598 police professionals (civilians and officers) from seven police services across Canada were surveyed. The survey was designed by Lum and Telep (n.d. Officer receptivity survey on evidence-based policing. Fairfax, VA: Center for Evidence-Based Crime Policy, George Mason University) to determine respondents’ knowledge of, and support for, evidence-based policing (EBP). Using their survey allowed us to compare our results to the data they collected in the U.S. Although Canadian respondents had similar concerns regarding EBP as those in the U.S., in several ways, Canadian police professionals were more open to the idea of EBP. The results are encouraging, but still suggest a lack of buy-in from some police professionals in certain regards. Potential reasons for the cross-national discrepancies, and the consequences of the findings, are discussed.